2022
DOI: 10.21093/ijeltal.v7i1.1182
|View full text |Cite
|
Sign up to set email alerts
|

Apologies and Compliment Responses: A Case of Pre-service EFL Teachers

Abstract: Apology may be defined as “a compensatory action for an offense committed by the speaker which has affected the hearer” (Marquez-Reiter, 2000, p. 44), and a compliment is another speech act "which explicitly or implicitly attributes credit to someone other than the speaker... which is positively valued by the speaker and the hearer" (Holmes, 1986, p. 485). The focus of this paper is to find out which strategies are employed by Turkish pre-service EFL (English as a Foreign Language) teachers while apologizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Korkmaz (2020) found that Turkish speakers relied on accepting the compliment as the dominant CR strategy and female speakers used fewer CRs than males. Turhan & Tuncer (2022) report that both male and female Turkish EFL pre-service teachers resorted to appreciation while responding to compliments. Yet, males preferred to receive praise upgrades more often than females who preferred to shift the credit to a third party.…”
Section: Introductionmentioning
confidence: 99%
“…Korkmaz (2020) found that Turkish speakers relied on accepting the compliment as the dominant CR strategy and female speakers used fewer CRs than males. Turhan & Tuncer (2022) report that both male and female Turkish EFL pre-service teachers resorted to appreciation while responding to compliments. Yet, males preferred to receive praise upgrades more often than females who preferred to shift the credit to a third party.…”
Section: Introductionmentioning
confidence: 99%